How Systems Form and How Systems Break A Beginner's Guide for Studying the World - Ren, Chiang H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Our world is composed of systems within systems-the machines we build, the information we share, the organizations we form, and elements of nature that surround us. Therefore, nearly every field of study and practice embodies behaviors stemming from system dynamics. Yet the study of systems has remained somewhat fragmented based on philosophies, methodologies, and intentions. Many methodologies for analyzing complex systems extend far beyond the traditional framework of deduction evaluation and may, thus, appear mysterious to the uninitiated. This book seeks to dispel the mysteries of systems analysis by holistically explaining the philosophies, methodologies, and intentions in the context of understanding how all types of systems in our world form and how these systems break. This presentation is made at the level of conceptual understanding, with plenty of figures but no mathematical formulas, for the beginning student and interested readers new to studying systems. Through the conceptual understanding provided, students are given a powerful capability to see the hidden behaviors and unexplained consequences in the world around us.
The Mysterious Discipline -- The Characteristics of Systems Formation -- The Characteristics of System Breakdown -- The Systems Analyst.
Keywords: Dynamics; Nonlinear theories; Multibody systems; Vibration; Mechanics, Applied; System theory; Control theory; Mathematical physics; Applied Dynamical Systems; Multibody Systems and Mechanical Vibrations; Complex Systems; Systems Theory, Control; Theoretical, Mathematical and Computational Physics